You Shamrock My World - Rossner, Rose; Smietanka, Ela ([Naperville, Illinois] : Sourcebooks Wonderland, 2022)
Rhyming wordplay celebrates St. Patrick's Day and assures little ones that they are loved.
new kids book 2022 winter.
Ages 0-4.
Grades K-1.
Keywords: Board books; Stories in rhyme; Plays on words -- Fiction; Board books; Saint Patrick's Day -- Fiction; Picture books; Stories in rhyme; Board books